(untitled) (Agricultural Engineering, 2020)
There are ca 1,492 thousand tractors currently used in Poland, with the average power of 45.3 kW. There are 9.8 ha of agricultural land per one tractor, their average age is ca 25 years and the degree of wear 77%. There are between 20 to 30 thousand tractors newly registered per year, however, these are both new and used tractors imported from abroad. These new registrations, which also reflect new purchases, are diverse depending on the region. Based on the 2018 records of the Central Register of Vehicles and Drivers (CEPiK), the paper establishes essential parameters of the registered tractors, such as price, power, age, depending on the region. There were 25,422 records under analysis, as some of the original records were dismissed as errors after verification. It was established that in the western part of Poland, with farms twice or three times bigger than in the rest of the country, the purchased tractors were characterized by higher power and lower age and, consequently, higher prices (81-95 kW, 14-18 years, PLN168-186 thousands). In contrast, the tractors in south-east Poland, where the dominant farms are of agricultural land below 10 ha, had worse parameters (76-86 kW, 14-18 years, PLN76-86 thousands).